Synthesis and Characterization of Oxozirconium(IV), Dioxomolybdenum(VI) and Dioxotungsten(VI) with Ciprofloxacin and Norfloxacin Complexes - Khalaf I. Khallow; Amaal Y. R. Al-Assaf (E-Journal of Chemistry)
The interaction of quinolone drugs, ciprofloxacin (CIPH) and norfloxacin (NORH), with zirconyl chloride octahydrate, sodium molybdate dihydrate and sodium tungstate dihydrate was investigated. Elemental analysis, FTIR spectral, electrical conductivity, magnetic susceptibility and UV Visible spectroscopy measurements have been used to characterize the isolated complexes. The results support the formation of two types of complexes of formula [ZrO(H2O)L2]3H2O and [MO2L2] where L = CIP and NOR; M = Mo and W. FTIR spectra of both types of complexes suggest that CIP and NOR act as deprotonated bidentate ligands through the ring carbonyl oxygen atom and one of the oxygen atom of carboxylic group.